Renewable energy: Bringing electricity to revitalize Africa’s rural areas - Arndt, Channing (International Food Policy Research Institute, 2019)
The world’s hundreds of millions of extremely poor people cannot escape from poverty without access to energy, notably electricity. The potential for new technologies to deliver electricity to poor and remote areas, most notably in Africa, is described in this chapter. The good news is that modern electrical systems, particularly solar power, are making it easier than ever to meet the energy needs of these populations. Costs of solar power systems have fallen dramatically and, given the high solar potential in many developing countries, these systems offer a host of rural livelihood, business, and development possibilities, as well as greater sustainability. With the right policies, real potential exists to ensure access to electricity for all by 2030.